UNGKAPAN PERASAAN DALAM KARYA LUKISKONTEMPORER - Rizalmi Pratama, Drs, Irwan, M.Sn., Dra. Jupriani, M.Sn. (Universitas Negeri Padang, 2016)
Unpleasent is a state of the soul in a person, as for thedelivery of state of the soul was sometimes in the form of a sense of love, such as tasty, delicious, happy, beautiful and so forth, sometimes in the form of taste do not like, such as nausea, irritated, restless fear and etc. Indirectly, feelings affect emotional state that usually emanated from gesture or body language. Man was given sense and reason to determine how the problems that have faced and will be facing him. Many factors influence the maturation process. A human being among others exam, disaster, sadness, sorrow, pleasure andhappiness.Feelings can bring someone on the positives and negatives. Positive things to say when a person is able to respondto the better and vice versa, negative things can change a person falls into a slump. Humans should take a lesson from everything that comes along the way, learn to accept the situation, learn to find the best solutions to problems faced.It became the inspiration for author and visualize intoworks of art, after passing through the observation and lengthyprocess. Inspired by life experiences that the authors feel. Everywork that appears to represent the issues and problems thathappened to the author himself. The desire of the author as creator is so that the work can be interpreted and useful for anyone.Keywords: Art Contemporary, Expression Feelings